MEMBANGUN KOMUNITAS RAMAH LINGKUNGAN MELALUI PEMBUATAN SABUN: ANALISIS PSIKOLOGI SOSIAL - Mahardika, Bagus; Roziqin, Nur Khoirur; Raihan, Afnan; Jaya, Raden Indra; Ar-razi, Muhammad Fakhri; Pertiwi, Yohana Putri; Amalia, Syafina Rahma; Febryanti, Thesa; Meilistika, Dwi; Aini, Yuli Nur; Durrotunafisah, Hasyimah (Abdimas IAI Ngawi, 2025)
Environmental sustainability is a must for humans to always maintain and care for nature to remain sustainable. Activities such as planting trees to green the hometown need to be cultivated so that the balance of the natural ecosystem continues to be maintained. Considering the importance of greening and providing skills education for the community, community service workers create activities to make environmentally friendly laundry soap from materials available in the surrounding environment such as lemongrass and teak leaves. This research activity was carried out in four stages, namely planning, implementation, observation and documentation. The results of the community service show an increase in public awareness to maintain and care for the environment, the community is able to make environmentally friendly soap and has a spirit of caring for the surrounding environment through the use of plants as economic value, besides that the community actively interacts and works together to advance the sustainability of the surrounding environment. Keywords: Environmentally Friendly Community, Social Psychology   Abstrak: Kelestarian lingkungan menjadi keharusan bagi umat manusia untuk selalu menjaga dan merawat agar alam tetap lestari. Kegiatan seperti menanam pohon untuk menghijaukan kampung halaman perlu dibudi dayakan agar supaya keseimbangan eksosistem alam terus terjaga. Mengingat pentingnya penghijauan dan memberikan edukasi kecakapan untuk masyarakat pengabdi membuat kegiatan membuat sabun cuci ramah lingkungan dari bahan-bahan yang ada dilingkungan sekitar seperti sereh dan daun jati. Kegiatan pengabdian ini dilakukan dengan empat tahapan yakni perencanaan, pelaksanaan, observasi dan dokumentasi. Hasil kegitan menunjukkan bertambahnya kesadaran masyarakat untuk menjaga dan merawat lingkungan, masyarakat mampu membuat sabun ramah lingkungan serta memiliki jiwa peduli lingkungan sekitar melalui pemanfaatan tanaman sebagai nilai ekonomis selain itu masyarakat aktif berinteraksi dan bergotong-royong memajukan kelestarian lingkungan sekitar. Kata Kunci: Komunitas Ramah Lingkungan, Psikologi Sosial